Interpreting Religious Radicalism in State Islamic Higher Education Institutions in East Java - Munradji; Nur Kholis; Siti Marpuah (Journal of Social Transformation and Regional Development, 2020)
This study aims to analyze the meaning and activities of religious radicalism in State Islamic Higher Education Institutions (PTKIN). The type of this research is qualitative through a phenomenological approach. Conducted in three State Islamic Higher Education Institutions (PTKIN), namely; IAIN Ponorogo, UIN Sunan Ampel Surabaya, and IAIN Madura, this study began in July until November 2019. The subjects of this research are students, lecturers, and academic staff as well as faculty leaders. The data collection process uses in-depth interview techniques, observation, and documentation. Data validity is carried out according to the degree of credibility, transferability, dependability, and confirmability. Data analysis was carried out in stages and interactively, starting with the activities; data reduction, data presentation, conclusion drawing, and verification. The results showed that; First, religious radicalism is interpreted as thoughts, attitudes, and behaviors urging comprehensive, fast, and revolutionary change in all aspects of the life of the society and nation. Radicalism is divided into three levels, namely; level of knowledge/understanding, attitudes, and behavior. Second, the programs and activities conducted by radical groups are exclusive, anti-government, and anti-colonialism. Western ideology and bourgeoisie practices in the secular government system are considered as the cause of injustice and poverty of society and nation.